Corporate Social Responsibility, Corporate Governance dan Manajemen Laba pada Perusahaan Manufaktur di Indonesia Tahun 2015-2019 - Cahyatih Kumandang; Nora Sri Hendriyeni (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to see how the influence of Corporate Social Responsibility (CSR) and Corporate Governance on earnings management practices. CSR is proxied by CSR award and Corporate Governance by GCG award. Earnings management is measured by discretionary accrual and real earning management through cash flow operations. The population in this study is all manufacture companies that listed in Indonesian Stock Exchange (BEI) which their financial reports are available completely during the study period, which is from 2015-2019. This study results shows that GCG has negative impact to accrual earnings management and real earnings management through cash flow operation even though its not significant, meanwhile CSR has negative impact to accrual earnings management and positive impact to real earnings management through cash flow operation and theyre not significant.